(untitled) (Bangladesh Journal of Plant Taxonomy, 2010)
A total 51 taxa of cyanophycean algae belonging to 28 genera have been enumerated from different lotic and lentic freshwater bodies of east Nepal during October, 2002 to June, 2004. Of these, 19 taxa were new additions to the cyanophycean flora of Nepal and 39 were new records for the study area. Coelosphaerium Nägeli, Fischerella (Bornet et Flahault) Gomont and Myxosarcina Printz were the first time describing genera for the country. Oscillatoria Vaucher ex Gomont has the maximum species observed in the study and were frequent in most of the samples too. The distribution pattern of cyanophycean algae according to different topography were as Terai>Mountain> Himalaya. Keywords: Algae; Cyanophyceae; Himalaya; East Nepal. DOI: 10.3329/bjpt.v17i2.6694 Bangladesh J. Plant Taxon. 17(2): 121-139, 2010 (December)